Skill mismatch in the Costa Rican labor market - Blanco, Laura Cristina (2019)
Skill mismatches are estimated using the National Household Survey 2011-2017, as defined by Chevalier (2003).  A logit multinomial analysis is used to study the covariates of skill mismatches and wage equations are analyzed as a function of the workers’ skill mismatches and competence levels.  The working adult population is found to have an underqualification level of 28.9%, while apparent and genuine overqualification levels are 13.3% and 0.8%, respectively.  Results show that underqualification is associated to a wage premium of about 30%, while apparent and genuine overqualification have a 35% and 47.5% wage penalty, respectively.  Graduates from tertiary institutions with an apparent overqualification level report a wage penalty of 38.9%, and it increases to 49.3% for those with a genuine overqualification level.